Multipleksowa detekcja gatunków Phytophthora przy użyciu platformy Fluidigm - Sikora, Katarzyna; Kubiak, Katarzyna; Malewski, Tadeusz; Nowakowska, Justyna; Oszako, Tomasz (Leśne Prace Badawcze, 2020)
The genus Phytophthora plays an important role not only in agriculture but also in forest ecosystems. As the number of known Phytophthora species continues to grow, identifying new isolates in this genus has become increasingly challenging even by DNA sequencing. Therefore, the development of proper techniques for detection and identification is crucial for monitoring and control of these pathogens in the forestry sector. In recent years, new molecular methods using innovative approaches have indeed been developed. However, the majority of these methods was designed to detect single Phytophthora species. Techniques that are able to target multiple species would offer advantages, especially for the assessment of Phytophthora diversity in the environment. This paper describes a multiplex assay for the identification of eight Phytophthora isolates, down to the species level, based on a Fluidigm platform employing pyrosequencing. The obtained results showed that for an accurate determination of the species, it is sufficient to know the sequence of two markers, ITS and COX1. The sensitivity of this test is sufficient to identify Phytophthora in a pure culture. Unfortunately, analysis based on a pyrosequencing platform does not provide enough data to simultaneous identify multiple Phytophthora species in samples collected in the field. This problem could be resolved in the future by sequencing using more efficient platforms like Illumina or IonTorrent.